La participación de los padres de familia y el lenguaje oral en los niños de la Institución Educativa Inicial N° 454 Mi Casita del Saber, Nauta 2022 - Piña Flores, Lady Corina (2023)
The main objective of this research was to determine the level of relationship between the participation of parents and oral language in children of the Initial Educational Institution No. 454 "Mi Casita del Saber" Nauta 2022. To achieve this, a relational approach and a non-experimental, field, correlational and transactional design. The study population was made up of all the boys and girls of both sexes, as well as the parents, and a census sample of 86 participants was selected. Survey and observation techniques were used, using a questionnaire and an observation guide as instruments to collect data, which were validated by expert judgment. The Tau_b de Kendall coefficient of consequences between the variables "participation of the parents" and "oral language of the children" turned out to be -0.018. This value indicates that the connection between the two variables is low, which leads to the conclusion that there is no significant relationship between the participation of parents and the oral language of children. Therefore, the null hypothesis is accepted and the alternate hypothesis is rejected.